Excess mortality at Christmas due to cardiovascular disease in the HUNT study prospective population-based cohort in Norway - Trine Moholdt; Clifford Afoakwah; Paul Scuffham; Christine F. McDonald; Louise M. Burrell; Simon Stewart (BMC, 2021)
Abstract Background Although it is known that winter inclusive of the Christmas holiday period is associated with an increased risk of dying compared to other times of the year, very few studies have specifically examined this phenomenon within a population cohort subject to baseline profiling and prospective follow-up. In such a cohort, we sought to determine the specific characteristics of mortality occuring during the Christmas holidays. Methods Baseline profiling and outcome data were derived from a prospective population-based cohort with longitudinal follow-up in Central Norway - the Trøndelag Health (HUNT) Study. From 1984 to 1986, 88% of the target population comprising 39,273 men and 40,353 women aged 48 ± 18 and 50 ± 18 years, respectively, were profiled. We examined the long-term pattern of mortality to determine the number of excess (all-cause and cause-specific) deaths that occurred during winter overall and, more specifically, the Christmas holidays. Results During 33.5 (IQR 17.1-34.4) years follow-up, 19,879 (50.7%) men and 19,316 (49.3%) women died at age-adjusted rate of 5.3 and 4.6 deaths per 1000/annum, respectively. Overall, 1540 (95% CI 43-45 deaths/season) more all-cause deaths occurred in winter (December to February) versus summer (June to August), with 735 (95% CI 20-22 deaths per season) of these cardiovascular-related. December 25th-27th was the deadliest 3-day period of the year; being associated with 138 (95% CI 96-147) and 102 (95% CI 72-132) excess all-cause and cardiovascular-related deaths, respectively. Accordingly, compared to 1st-21st December (equivalent winter conditions), the incidence rate ratio of all-cause mortality increased to 1.22 (95% CI 1.16-1.27) and 1.17 (95% 1.11-1.22) in men and women, respectively, during the next 21 days (Christmas/New Year holidays). All observed differences were highly significant (P < 0.001). A less pronounced pattern of mortality due to respiratory illnesses (but not cancer) was also observed. Conclusion Beyond a broader pattern of seasonally-linked mortality characterised by excess winter deaths, the deadliest time of year in Central Norway coincides with the Christmas holidays. During this time, the pattern and frequency of cardiovascular-related mortality changes markedly; contrasting with a more stable pattern of cancer-related mortality. Pending confirmation in other populations and climates, further research to determine if these excess deaths are preventable is warranted.